2019
DOI: 10.1038/s41598-019-51539-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding traffic capacity of urban networks

Abstract: Traffic in an urban network becomes congested once there is a critical number of vehicles in the network. To improve traffic operations, develop new congestion mitigation strategies, and reduce negative traffic externalities, understanding the basic laws governing the network’s critical number of vehicles and the network’s traffic capacity is necessary. However, until now, a holistic understanding of this critical point and an empirical quantification of its driving factors has been missing. Here we show with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(85 citation statements)
references
References 37 publications
4
81
0
Order By: Relevance
“…omplex engineered systems are known to exhibit unintended states in their collective dynamics that often disrupt their function [1][2][3][4][5] . In complex mobility systems, examples include the emergence of congestion 6,7 , anomalous random walks in human travel patterns 8 , and cascading failures of mobility networks [9][10][11] . As urban mobility becomes more and more self-organized and digitized, mobility services increasingly employ dynamic pricing [12][13][14][15][16] , in general serving two main purposes ( Fig.…”
mentioning
confidence: 99%
“…omplex engineered systems are known to exhibit unintended states in their collective dynamics that often disrupt their function [1][2][3][4][5] . In complex mobility systems, examples include the emergence of congestion 6,7 , anomalous random walks in human travel patterns 8 , and cascading failures of mobility networks [9][10][11] . As urban mobility becomes more and more self-organized and digitized, mobility services increasingly employ dynamic pricing [12][13][14][15][16] , in general serving two main purposes ( Fig.…”
mentioning
confidence: 99%
“…Please note that one advantage of the NFD-based approach is that no DTA is generally necessary. The NFD can be estimated based on loop detector or floating car data [33], [34]. In the absence of data, analytical estimation methods can be applied to derive the NFD [35]- [38].…”
Section: Network Fundamental Diagrammentioning
confidence: 99%
“…Geroliminis and Daganzo (2008) confirmed the existence of the MFD by linking the vehicle accumulation to the average flow in a network with data from San Francisco and Yokohama. Recently, strong evidence for the unimodal MFD was reported for an extensive list of cities (Loder et al, 2019a). Moreover, first studies reported of the empirical evidence for the multi-modal MFD.…”
Section: Introductionmentioning
confidence: 99%